EFEKTIVITAS PENGGUNAAN MEDIA VIDEO PEMBELAJARAN DI RANAH SEKOLAH DASAR DALAM METODE PEMBELAJARAN ELEKTRONIK - Tri Septianing Wardanti (Jurnal Pendidikan Dasar Borneo (Judikdas Borneo), 2021)
This study aims to determine the difference in the effectiveness of other learning methods with learning methods using SD thematic learning videos in the Pembelajaran elektronik method. This study uses a meta-analysis research type, namely using several studies that have been conducted. This research method is quantitative. This study aims to determine the effectiveness of using SD Thematic Learning Video Media in the Pembelajaran elektronik Method. Research data collection was carried out by searching Google Scholar using the keywords effectiveness, instructional video media, thematic, elementary students, and Pembelajaran elektronik. The results of the analysis show that the use of SD thematic learning videos in the Pembelajaran elektronik method has increased interest in learning from the lowest 14.08% to the highest 76.18% with an average of 40.86%.Keywords: effectiveness, instructional video media, thematic, elementary students, and E-Learning